ALJAŽ PEGAN GYMNASTIC RESULTS DEVELOPMENT AT WORLD CHAMPIONSHIPS - Andrej Kunčič; Jože Mešl (Science of Gymnastics Journal)
In article we overview 19 years of a 33 year long sporting career of the gymnast Aljaž Pegan. His scores, ranks and exercises on the horizontal bar are presented for each World Championship. Exercises are further broken down into individual elements and descriptions of those elements. They are presented in accordance with the Code of Points published by Federation International Gymnastics, which was in force for a particular four-year period, and a theoretical comparison was made, taking into account all the changes and adjustments, with the Code of Points 2013-2016. Additionally, breakdowns of the seven Codes of Points for the horizontal bar which were in force in the period from 1989 to 2013 are also shown. Adaptation to the changing criteria of the Code of Points can be seen in the exercises through upgraded elements, which Aljaž could grasp due to his exceptional knowledge of basic motor structures such as: free hip circles, giant swings, flights and elements in double el-grip. During his career Aljaž and his coach invented two unique elements that bear his last name in the Code of Points, Pegan on the horizontal bar and on the parallel bars. His greatest success was at the World Championship in Melbourne, Australia in 2005, where he became the World Champion on the horizontal bar.